Advancements in the study of neural mechanisms underlying mammalian grouping behaviour - Kelly, Aubrey M. (Frontiers in Ethology, 2023)
Despite the prevalence of large group-living in the animal kingdom, we know surprisingly little about how the brain facilitates grouping behavior, particularly in mammals. In this brief communication, I provide an update on advancements in the study of the neural mechanisms underlying mammalian grouping behavior. I discuss the benefits of using non-traditional organisms in the laboratory and provide examples of how using non-standard, large housing and testing apparatuses produces more ethologicallyrelevant behavioral datasets. Further, with advancements in computer vision-based automated tracking and increasing availability of wireless neural recording and manipulation tools, scientists can now generate unprecedented neurobehavioral datasets from multiple interacting animals. Together, recent advancements in behavioral and neural approaches hold great promise for expanding our understanding of how the brain modulates complex, mammalian grouping behaviors.